2014
DOI: 10.1186/1472-6963-14-379
|View full text |Cite
|
Sign up to set email alerts
|

What limits the utilization of health services among the rural population in the Dabie Mountains- Evidence from Hubei province, China?

Abstract: BackgroundIndividuals living in rural mountain areas tend to use health services less to manage discomfort or illness. This study aims to identify the variables that best explain the health service utilization of a sample of the rural population in the Dabie Mountains in China.MethodsTo obtain information about health service utilization, a cross-sectional household survey was conducted using face-to-face interviews among the residents of a poor town in the Dabie Mountains. A total of 1,003 residents aged 15 o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
33
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(40 citation statements)
references
References 25 publications
6
33
0
1
Order By: Relevance
“…Moreover, we found that the effects of economic status and altitude were not simply additive (especially in the model for predicting Ph/inhab): wealthier municipalities had a higher density of pharmacies, but this relationship depended on height, being significant only in locations at a relatively high altitude. These findings are also consistent with previous studies on healthcare services (Liu et al, 2011;Fang et al, 2014). Fang et al (2014) have in fact established that economic determinants influence the utilisation of healthcare services to a greater extent in mountainous regions than in the plains.…”
Section: Key Findings and Comparison With Previous Researchsupporting
confidence: 92%
See 2 more Smart Citations
“…Moreover, we found that the effects of economic status and altitude were not simply additive (especially in the model for predicting Ph/inhab): wealthier municipalities had a higher density of pharmacies, but this relationship depended on height, being significant only in locations at a relatively high altitude. These findings are also consistent with previous studies on healthcare services (Liu et al, 2011;Fang et al, 2014). Fang et al (2014) have in fact established that economic determinants influence the utilisation of healthcare services to a greater extent in mountainous regions than in the plains.…”
Section: Key Findings and Comparison With Previous Researchsupporting
confidence: 92%
“…These findings are also consistent with previous studies on healthcare services (Liu et al, 2011;Fang et al, 2014). Fang et al (2014) have in fact established that economic determinants influence the utilisation of healthcare services to a greater extent in mountainous regions than in the plains. Analogously, Liu et al (2011) have reported that maternal healthcare utilisation is closely related to both wealth and altitude.…”
Section: Key Findings and Comparison With Previous Researchsupporting
confidence: 92%
See 1 more Smart Citation
“…These findings corroborate the results of a study conducted with a Korean population [ 26 ], which found that the prevalence of musculoskeletal, and therefore physical, discomfort was higher among women with lower incomes, similar to the women in the present study, who have an average family income of BRL 1500.00 and a per capita income of BRL 500.00. In addition, higher income levels reduced the chance of experiencing physical discomfort by 2%, that is, income served as a protective factor against physical discomfort; this is in line with the results of a study on individuals from agricultural areas in China, which sought to identify the variables that explained the use of health services [ 27 ].…”
Section: Discussionsupporting
confidence: 55%
“…These determinants could include social support/hospital accompaniment (e.g., whether a PLCD has someone to accompany them when go to the hospital) and primary hospitals (e.g., village clinic; community or township hospitals) as the usual source of care. In sum, current evidence on health-seeking behaviors and positive self-maintenance of chronic conditions for PLCD in China have focused too narrowly on the patterns of health service utilization [24] and willingness to use health services [3,9]. There is, however, limited understanding the individual- and social-level factors that are associated with regular utilization of healthcare services by PLCD.…”
Section: Introductionmentioning
confidence: 99%